Antibióticos sistémicos en periodoncia - Velasquez-E., Hernando; Botero-Z., Leticia; Alvear-E., Fanny S. (Revista Facultad de Odontología Universidad de Antioquia, 2016)
There is evidence that specific bacteria produce particular forms of periodontal disease. Currently, plenty of investigations are focused on effective antibiotic regimens to control those microorganisms, used in combination with conventional manual procedures as root planning, scaling and periodontal surgery. The most used antibiotics in the treatment of periodontal diseases are tetraciclines, mainly in cases of Localized juvenile Periodontitis (PO Penicillins have a limited effect, but Amoxacilin combined with potassic Clavulanate has shown to be useful in cases of Refractory Adult Periodontitis, when microflora is basically Gram (+). Metronidazole may be effective in Adult Chronic Periodontitis, when flora is strictly anaerobe. Used in combination with Amoxacilin is useful for the elimination of A. actinotnycetemcomitans. Clindamicin is an useful alternative for Refractory Periodontitis associated principally with Grain (-) flora. There is a discussion on antibiotic therapy in periodontics, and its conclusion is that there is no clear support for the antibiotic rutinary treatment of Adult Periodontitis.